Phenotypic variability of Smallanthus sonchifolius germplasm of Peru - Santa Cruz Padilla, Angel Esteban (2025)
Smallanthus sonchifolius (yacon) is a functional food native to the South American Andes. Its tuberous root and leaves are the main parts consumed; however, few studies have been carried out on its phenotypic variability. This study aimed to characterize 214 yacon accessions from the Germplasm Bank of the Instituto Nacional de Innovación Agraria (INIA), Peru. Twelve qualitative and seven quantitative variables were used. Accession Y-74 showed the largest leaf dimensions, while Y-28 showed the highest productivity per plant. Multiple correspondence analysis and principal component analysis revealed that the variables propagule color, leaf shape, root pulp color, leaf length and width, root weight per plant, and yield contributed significantly to the discrimination and identification of promising accessions. The geographical grouping of the accessions showed differences between accessions from the north and south of Peru. The qualitative phylogenetic tree showed 12 morphological groups discriminated mainly by leaf morphology and root characteristics, while the dendrogram analysis identified four clusters, with Cluster II standing out with an average yield of 73.5t/ha of tuberous roots. These results are important, as they allowed the identification of promising accessions and useful traits that can contribute to improving productivity and promoting the expansion of yacon cultivation at national and international levels.